2012
DOI: 10.1002/ajmg.a.35309
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in patients with hereditary hemorrhagic telangiectasia in Norway: A population based study

Abstract: Hereditary hemorrhagic telangiectasia (HHT) is a rare, autosomal dominant disease characterized by the presence of recurrent epistaxis and small characteristic malformations of the peripheral blood vessels near the surface of the skin or mucosal linings. Arteriovenous malformations (AVM) of the lung, liver, and CNS are also known clinical findings. The purpose of this study was to examine quality of life (QoL) in patients with HHT in Norway. Sixty-six affected patients (39 women and 27 men) were included. QoL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 27 publications
2
41
1
Order By: Relevance
“…However, this finding is consistent with previous studies of patients with HHT in Norway and Germany. First, 58 % reported that HHT symptoms negatively impacted their QoL (Geirdal et al 2012). Second, this study confirmed work as the primary area of everyday life affected by HHT (Geirdal et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, this finding is consistent with previous studies of patients with HHT in Norway and Germany. First, 58 % reported that HHT symptoms negatively impacted their QoL (Geirdal et al 2012). Second, this study confirmed work as the primary area of everyday life affected by HHT (Geirdal et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…First, 58 % reported that HHT symptoms negatively impacted their QoL (Geirdal et al 2012). Second, this study confirmed work as the primary area of everyday life affected by HHT (Geirdal et al 2012). A subset of German patients with HHT reported that experiencing nosebleeds led to a career change (Geisthoff et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations